PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH KREDIT KONSUMTIF: CITRA BANK DAN KEPUASAN NASABAH SEBAGAI VARIABEL MEDIATOR - Sefnedi Sefnedi (Universitas Paramadina, 2014)
The banking sector plays an important role to support economic growth. However, nowadays the banking industry is facing keen competition. The success of the bank in order to win the competition is determined by customer loyalty. One of bank that is fully aware of the high level of competition in the banking industry and the importance of customer loyalty is the Jambi Bank Branch Sungai Penuh. Among the broad factors that are able to impact customer loyalty namely banking image, customer satisfaction and service quality. The purpose of this research is to investigate the role of banking image and customer satisfaction as mediator variables on the relationship between service quality and customer loyalty. The population of this study is all customers of consumptive loans at Jambi Bank Branch Sungai Penuh which accounted for 371 customers. The numbers of useful samples were 193 customers by performing proportional cluster random sampling method. In order to conduct hypotheses development, this research performs simple, multiple and hierarchical regression analyses by using Statistical Package for Social Science (SPSS) version 19.0. The results of analysis display that 1) Service quality positively and significantly impacts customer loyalty. 2) Service quality positively and significantly impacts banking image. 3) Service quality positively and significantly impacts customer satisfaction. 4) Banking image and customer satisfaction positively and significantly impact customer loyalty 5) Banking image and customer satisfaction are found as full mediator on the relationship between service quality and customer loyalty. The results of the study provide practical implication to head office of Jambi Bank Branch Sungai Penuh that in order to increase the level of customer loyalty future, it is recommended to enhancing banking image, customer satisfaction as well as service quality.